BROAD SPECTRUM ANTIMICROBIAL ACTIVITIES OF ISOLATED ALLICIN - F.REHMAN; SAMYA MAIRAJ (International Journal of Pharma and Bio Sciences, 2014)
The pharmaceutical importance of Allium Sativum is due to the presence of carbohydrate, protein ,vitamins, essential metal and organosulphur compounds. Allicin is one of the active ingredient of freshly crushed garlic homogenates and showed a wide spectrum activity. The antimicrobial activity of different concentration of allicin against gram positive and gram negative bacterial isolate was studied by standard protocols. The maximum zone of inhibition has been observed in S. typhi and minimum for E. Coli. The minimal inhibitory concentration (MIC) varies bacteria to bacteria and fungus to fungus respectively. The effect of time, temperature and pH were also studied. The antibacterial efficacy was maintained at room temperature for maximum one week and maintains for longer time only at low temperature. Antimicrobial activity of garlic come from allicin, is mainly due to S-S and S-O bond which has the ability to react with thiol containing enzyme to form S-thiolation product, the broad spectrum antimicrobial effects of allicin is due to the multiple inhibitory effects on various thiol dependent enzymatic systems. The results indicate that allicin has antimicrobial activity.